Multi-hazard analysis of flood and tsunamis on the western Mediterranean coast of Turkey - C. Yavuz; K. Yilmaz; G. Onder (Natural Hazards and Earth System Sciences, 2022)
Flooding has always been a devastating hazard for social and economic assets and activities. Especially, lowland areas such as coastal regions can be more vulnerable to inundations. The combination of different natural hazards observed at the same time is definitely worsening the situation in the affected regions. The goal of this study is to conduct a distinctive multi-hazard analysis considering flood hazards with the contribution of potential earthquake-triggered tsunamis that might be observed throughout the Fethiye coastline and city center. For this purpose, tsunami hazard curves are generated based on Monte Carlo simulations. Comprehensive stochastic hazard analyses are performed considering the aleatory variability of earthquake-triggered tsunamis and epistemic uncertainty of floods having 10-, 50-, and 100-year return periods. Numerical simulations are conducted to combine the potential tsunamis and flood events that are able to adversely affect the selected region. The results of this study show that the blockage of stream outlets due to tsunami waves drastically increases the inundated areas and worsens the condition for the selected region.